Anti-inflammatory and antioxidant properties of unripe papaya extract in an excision wound model - Nafiu, Abdulrazaq Bidemi; Rahman, Muhammad Tariqur (Informa Healthcare, 2015)
Context: Carica papaya L. (Caricaceae) fruit was shown to exhibit wound healing properties. Objectives: We investigated anti-inflammatory and antioxidant potential of papaya fruit phosphate-buffered saline extract (PE) during wound healing and enhancement of the potentials due to trace ions addition. Materials and methods: Rat excision wounds were topically treated twice/day with 20 μL of PE (5 mg extract/mL), 0.5 μg Se2+ added PE (PES), or 100 μM Zn2+ added PE (PEZ). Control groups were treated with deionized water (negative) and deproteinized calf blood extract ointment (Solcoseryl®, positive). Lipid peroxidation (LPX), antioxidant, proinflammatory, and arginine metabolic enzymes were estimated in the wound excised on days 4 and 10 post wounding. Results: PE (5 mg/mL; 9.80 ± 0.33 d) and PES (PE + 0.5 μg Se2+; 8.90 ± 0.23 d) significantly (p < 0.05) reduced the average time for complete wound closure compared with the negative (13.00 ± 0.37 d) and positive (9.80 ± 0.33 d) controls, respectively. Biochemical evaluations of LPX product (malondialdehyde), antioxidant (catalase, superoxide dismutase (SOD), and glutathione peroxidase (GPx)), and pro-inflammatory (cyclooxygenase-2 and myeloperoxidase (MPO)) enzyme activities and metabolites (nitrite and urea), on days 4 and 10 post wounding, confirmed the anti-inflammatory and antioxidant properties of PE and PES in this study. Discussion and conclusion: Treatment of excision wounds with papaya extract, especially with the addition of selenium for 10 d, reduced inflammation associated oxidative damage apparently via cyclooxygenase specific inhibition, arginine metabolism, and up-regulation of antioxidant enzymes.